Who likes in the end? Methods for improving the safe use of the internet = Kto w końcu lubi? Sposoby podniesienia bezpieczeństwa podczas korzystania z internetu - Bene, Viktoria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Educators and social experts must face a new challenge caused by the digital revolution. The online sphere, especially social media, plays an important role in young people?s lives. Due to the Internet, they can easily gain information, use their creativity and create vlogs and blogs. On the other hand, the Internet has a dark side, which consists in cyberbullying, fake news and self-esteem issues.
Keywords: training methods; Internet safety; ICT devices; cyberbullying; metody kształcenia; bezpieczeństwo w Internecie; urządzenia ICT